Peran Guru dalam Kebijakan Merdeka Belajar dan Implementasinya terhadap Proses Pembelajaran di SMP Negeri 1 Pancur Batu - Muhammad Iqbal; Arya Winanda; Dwika Hanum Sagala; Utia Rahmadani Ar Hasibuan; Wirahayu Wirahayu (Departement of Mathematics Education, 2023)
The essence of independent learning is the freedom of teachers and students in the learning process. This freedom has not been experienced by teachers and students so far because teachers are more concerned with the administration of education and learning. Teachers also do not understand the concept and its role in the independent learning policy. The purpose of this study was to determine the teacher's role in the independent learning policy and its implementation in the learning process at SMP Negeri 1 Pancur Batu. The reasons behind the emergence of this research are none other than seeing the current independent learning policy as something new for the world of education. The role of the teacher varies widely, including independent learning facilitators, innovative and creative teachers, teachers with characteristics as teachers, and driving teachers. Based on these explanations, this study concluded that understanding the meaning of independent learning and the teacher's role in independent learning helps teachers and students to be more independent in thinking, more innovative and creative, and happy in learning activities. The research method used is a qualitative approach. While the data was collected through library research methods (library research).